Innovations in noninvasive sensory stimulation treatments to combat Alzheimer's disease. - Jung M Park; Li-Huei Tsai (PLoS Biology)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder affecting millions worldwide. There is no known cure for AD, highlighting an urgent need for new, innovative treatments. Recent studies have shed light on a promising, noninvasive approach using sensory stimulation as a potential therapy for AD. Exposing patients to light and sound pulses at a frequency of 40 hertz induces brain rhythms in the gamma frequency range that are important for healthy brain activity. Using this treatment in animal models, we are now beginning to understand the molecular, cellular, and circuit-level changes that underlie improvements in disease pathology, cognition, and behavior. A mechanistic understanding of the basic biology that underlies the 40-hertz treatment will inform ongoing clinical trials that offer a promising avenue of treatment without the side effects and high costs typically associated with pharmacological interventions. Concurrent advancements in neurotechnology that can also noninvasively stimulate healthy brain rhythms are illuminating new possibilities for alternative therapies. Altogether, these noninvasive approaches could herald a new era in treating AD, making them a beacon of hope for patients, families, and caregivers facing the challenges of this debilitating condition.